Internal Migration and House Prices in Australia - Isil Erol; Umut Unal (Philipps-University Marburg, School of Business and Economics, 2021)
Australia is one of the most mobile countries in the world through internal migration, which is an overlooked part of population change. This study provides the first empirical evidence for the impact of internal migration inflow on house price changes across 237 statistical regions in Australia from 2014 to 2019. Employing a spatial correlation approach and constructing a novel instrumental variable that matches the shift-share instrument used in the immigration literature, the paper indicates that population mobility increases housing prices in migration receiving regions. Internal migration that amounts to 1% of the initial local area population is associated with a 0.7% to 0.8% increase in house prices in the three most populated states of Australia. The results provide further suggestive evidence that migration inflow has a significant positive effect on house price changes in metropolitan areas of New South Wales and Victoria – i.e., Capital Cities of Sydney and Melbourne – rather than non-metropolitan regions.
Keywords: R12; R23; R31; 330; Internal migration; Housing prices; Australia; Instrumental variables